Determinantes de las exportaciones ecuatorianas no petroleras hacia los Estados Unidos de América en el período 2007-2021. - Ramos Castelo, Lisseth Katherine (2023)
The majority of Ecuadorian exports have been reported as being of an oil nature, taking into account that oil is a resource limited in time, it is necessary to emphasize the supply of exports with other types of goods. In previous studies on determinants of exports they have been considered in a general way, ignoring how each determinant affects at the product level and, above all, in the US market. In this way, the present study identifies the factors that explain the behavior of Ecuador’s non-oil exports to the United States of America in the period 2007-2021, after conducting a brief analysis of the selected export products; banana, shrimp, cocoa, flowers, and the application of an autorregressive model of distributed delays (ARDL). The main results indicate that external demand is the most influential variable for bananas and flowers, while, for shrimp and cocoa, it is the exchange rate (ITCBR) with Colombia in the long term. Meanwhile, in the short-term exports of bananas, cocoa and flowers were influenced by the same exports with lags of 2 and 3 quarters. The elasticity of the GNI was positive at levels and with 2 quarters of delay for shrimp, indicating a high dependence of exports of this crustacean with respect to US GNI, a fictitious variable was included to represent the pandemic period given the highly increasing behavior of Ecuadorian shrimp exports in the US market. In addition, the TCRB with Colombia was significant for cocoa exports at levels 1 and 3 quarters behind. Finally, in terms of public credit, this was positive and significant for cocoa, at levels 1 and 2 lagging behind.